Randomized tax deadlines can help economy - Julio Urenda; Olga Kosheleva (Asian Journal of Economics and Banking (AJEB), 2024)
Purpose - While the main purpose of reporting - e.g. reporting for taxes - is to gauge the economic state of a company, the fact that reporting is done at pre-determined dates distorts the reporting results. For example, to create a larger impression of their productivity, companies fire temporary workers before the reporting date and re-hire then right away. The purpose of this study is to decide how to avoid such distortion. Design/methodology/approach - This study aims to come up with a solution which is applicable for all possible reasonable optimality criteria. Thus, a general formalism for describing and analyzing all such criteria is used. Findings - This study shows that most distortion problems will disappear if the fixed pre-determined reporting dates are replaced with individualized random reporting dates. This study also shows that for all reasonable optimality criteria, the optimal way to assign reporting dates is to do it uniformly. Research limitations/implications - This study shows that for all reasonable optimality criteria, the optimal way to assign reporting dates is to do it uniformly. Practical implications - It is found that the individualized random tax reporting dates would be beneficial for economy. Social implications - It is found that the individualized random tax reporting dates would be beneficial for society as a whole. Originality/value - This study proposes a new idea of replacing the fixed pre-determining reporting dates with randomized ones. On the informal level, this idea may have been proposed earlier, but what is completely new is our analysis of which randomization of reporting dates is the best for economy: it turns out that under all reasonable optimality criteria, uniform randomization works the best.
Keywords: 330; Disruption caused by fixed reporting dates; Optimal distribution of reporting dates; Randomized reporting dates; Tax reporting